2014
DOI: 10.1002/2014jf003155
|View full text |Cite
|
Sign up to set email alerts
|

Exploring landscape sensitivity to the Pacific Trade Wind Inversion on the subsiding island of Hawaii

Abstract: The interaction of the subsiding limb of the Hadley circulation and the easterly North Pacific Trade Winds establishes a persistent thermal inversion at about 2000 m above sea level in the subtropical Pacific. The inversion restricts convective rainfall to the lower elevations of the windward flank of the island of Hawaii, creating an order-of-magnitude vertical rainfall gradient, as well as high interbasin variability in precipitation. In the high-rainfall zone, streams are incised tens to hundreds of meters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…13). This argument is also in accordance with an earlier study about the detachment-limited condition (Whipple and Tucker, 1999). Note that the inverse relationship between the imposed P and the resultant relief is found to be nonlinear (as P linearly grows from 50 to 100 and 150 mm d −1 , relief reduces nonlinearly, approximately from 2.7 to 1.5 and 1 km).…”
Section: No-feedback Simulationssupporting
confidence: 92%
“…13). This argument is also in accordance with an earlier study about the detachment-limited condition (Whipple and Tucker, 1999). Note that the inverse relationship between the imposed P and the resultant relief is found to be nonlinear (as P linearly grows from 50 to 100 and 150 mm d −1 , relief reduces nonlinearly, approximately from 2.7 to 1.5 and 1 km).…”
Section: No-feedback Simulationssupporting
confidence: 92%
“…Yet when the model assumptions are tested with independent field evidence, disparate conclusions are reached. In some cases, researchers have interpreted that the model captures the dynamics of mountainous rivers reasonably well (Crosby & Whipple, ; Cyr et al, ; DiBiase et al, ; Duvall et al, ; Ouimet et al, ; Snyder et al, ), yet in other studies, researchers found that the model fails to predict morphological changes associated with a significant variation in forcing (Cowie et al, ; Lague, ; Lavé & Avouac, ; Ward & Galewsky, ; Whittaker et al, ; Yanites et al, ). Developing new quantitative approaches that can bridge the gaps in the observational tests of theory is needed to improve constraints on how topography evolves in a dynamic Earth system.…”
Section: Introductionmentioning
confidence: 99%
“…Within large river basins, these differences may be substantial. Exposure to orographic precipitation patterns is expected to systematically affect river profile concavity; increases in precipitation with distance upstream lowers profile concavity, while the opposite trend increases profile concavity (Han et al, 2014(Han et al, , 2015Roe et al, 2002Roe et al, , 2003Ward & Galewsky, 2014). Changes in concavity driven by temporal changes in orographic precipitation patterns require longitudinally variable amounts of incision.…”
mentioning
confidence: 99%